Electrochemical impedance and spectroscopy study of the EDC/NHS activation of the carboxyl groups on poly(ε-caprolactone)/poly(m-anthranilic acid) nanofibers - Z. Guler; A. S. Sarac (eXPRESS Polymer Letters)
Electrochemical impedance spectroscopy (EIS) and spectroscopy was applied to investigate the surface activation of carboxyl group (–COOH) containing nanofibers by the reaction of 1-ethyl-3-(dimethyl-aminopropyl) carbodiimide hydrochloride (EDC)/N-hydroxyl succinimide (NHS) in different concentrations. Poly(!-caprolactone)/poly(m-anthranilic acid) (PCL/P3ANA) nanofibers were fabricated by electrospinning and were activated with 5/0.5, 0.5/5, 5/5 and 50/50 mM of EDC/NHS. The surface activation was investigated by Attenuated Total Reflectance Fourier transform infrared spectroscopy (FTIR-ATR) and activation yield was estimated. Albumin was immobilized after surface activation and the amount of covalently immobilized protein was determined by bicinchoninic acid (BCA) assay. Morphology and composition of albumin immobilized nanofibers were characterized by Scanning Electron Microscopy/Energy-Dispersive X-ray Spectroscopy (SEM/EDX) and Atomic force microscope (AFM). EIS measurements indicated that nanofibers become resistant after albumin immobilization. The obtained data revealed that the highest amount of albumin bound to nanofibers activated with 50/50 mM of EDC/NHS which was found to be the optimum concentration for the activation of PCL/P3ANA nanofibers.